Penggunaan Aplikasi Appsheet untuk Katalog UMKM di Kelurahan Gedog, Kecamatan Sananwetan, Kota Blitar - Dewi Puspa Arum; Firdha Amalia Nareswari; Ega Dhija Ditriyo; Tri Prasetyo Ramadani; Diva Jannati Az Zahra; Syahrie Maulana Ramadhan (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
The development of increasingly sophisticated technology has become an asset for business development, especially for newly developed Small Medium Enterprises. With the rapid development of information technology, data processing is also getting faster. For this reason, Gedog Village needs technology that makes it easier between consumers and distributors. Therefore, we use this Appsheet application to create an online MSME catalog that is easily accessible to the public in the Gedog Village. The use of a website-based application can increase productivity in viewing the sales catalog of MSMEs in the Gedog village. Appsheet is an application that can be used to create a catalog application. Of course, with the addition of other applications such as Google Drive and Google Sheets. Some of these applications can be put together to create an application that can later be used to catalog MSMEs in Gedog Village, Blitar City.